A Glyptagnostus reticulatus trilobite faunule from the Cambrian of the Northern Qilian Mountains, northwest China, and its paleogeographical implications. (July 2022) - Zhu, Xuejian; Hughes, Nigel C.; Zhou, Zhiqiang
Abstract: A Glyptagnostus reticulatus (Angelin, 1851 )–bearing trilobite assemblage has been found from an unnamed Cambrian formation in the Northern Qilian Mountains area, of which geographical placement in the Cambrian is contested. Glyptagnostus reticulatus is a biostratigraphic indicator of the Furongian Series and Paibian Stage, and three agnostoid and six polymerid taxa from the Changgou section, Daliang area are described herein, along with conspecific forms from the nearby Chuancigou section. This well-preserved assemblage shows strong taxonomic affinity with northwestern Queensland, Australia, and western Hunan–eastern Guizhou, China, and likely comes from deep outer-shelf to slope setting associated with the Northern Qilian arc. It is consistent with other arguments that during the Cambrian, the Northern Qilian arc, along with the Hexi Corridor of the Alxa terrane, were more closely allied to South China than to North China.